2019
DOI: 10.1159/000494711
|View full text |Cite
|
Sign up to set email alerts
|

Could there be Haemodynamic Stress Effects on Pro-Inflammatory CD14+CD16+ Monocytes during Convective-Diffusive Treatments? A Prospective Randomized Controlled Trial

Abstract: Background: The main aim is to compare the pro-inflammatory CD14+CD16+ monocytes blood levels in patient in end-stage renal disease (ESRD) undergoing Mixed online Haemodiafiltration (Mixed OL-HDF) vs. post-dilution OL-HDF and online high-efficiency haemodialysis. Methods: The study is a prospective double-blind randomized controlled cross-over trial. Dialysis monitor, membrane, duration and dialytic adequacy, volume ultrapure dialysate/infusion were the same in all treatments. Monocyte CD14+CD16+, CD14-CD16+, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In addition to differences in clearance of retention solutes, biophysical aspects of the treatment might be relevant as well. This was suggested by a recent trial comparing mixed vs. postdilution HDF [66]. Potentially, the different hemoconcentration and shear stress contributed to the monocyte population distribution.…”
Section: Monocyte Subpopulationsmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition to differences in clearance of retention solutes, biophysical aspects of the treatment might be relevant as well. This was suggested by a recent trial comparing mixed vs. postdilution HDF [66]. Potentially, the different hemoconcentration and shear stress contributed to the monocyte population distribution.…”
Section: Monocyte Subpopulationsmentioning
confidence: 96%
“…Studies on different dialysis modalities found conflicting results. While online-hemodiafiltration (HDF) was reported to reduce the Mo2 population [66][67][68], this could not be demonstrated for high cut-off hemodialysis [69] in prospective trials. In addition to differences in clearance of retention solutes, biophysical aspects of the treatment might be relevant as well.…”
Section: Monocyte Subpopulationsmentioning
confidence: 99%
“…The potential role of different dialysis techniques in modulating monocytes' phenotype and function has been investigated with conflicting results. Some authors reported a reduction in the Mo2 population in patients treated with online hemodiafiltration, when compared to standard HD, without differences between pre-, mixed, or post-dilution [61,62].…”
Section: Neutrophils and Monocyte Macrophagesmentioning
confidence: 99%
“…Hypercatabolism in dialysis patients is related to intradialytic loss of amino acids as well as cytokine activation [ 91 , 92 ]; interleukin-6 plays a central role in regulating whole-body, muscle and hepatic protein turnover during hemodialysis. CD14 + CD16 + lymphocytes play a central role in the release of cytokines (IL-1 IL-6, TNF-α) [ 93 ]. Furthermore, at the end of the session, a post-dialysis rebound of numerous molecules occurs, the most widely studied of which is urea, largely due to the ease of detection.…”
Section: Nutritional and Therapeutic Interventionsmentioning
confidence: 99%